Identification of alpha-substituted acylamines as novel, potent, and orally active mGluR5 negative allosteric modulators. Issue 16 (15th August 2015) - Yoshikawa, Keita; Ohyama, Tomofumi; Takahashi, Eiki; Numajiri, Yoshitaka; Konno, Mitsuhiro; Moriyama, Masaki; Takemi, Natsumi; Kunita, Kana; Nishimura, Kazumi; Hayashi, Ryoji
Graphical abstract